Pengaruh Pemberian Head Up terhadap Nyeri Kepala Pasien Pasca Operasi dengan Spinal Anestesi - Suhadi Suhadi; Heni Purwaningsih; Oneys Syekh Putra (Pusat Riset dan Inovasi Nasional, 2022)
Background: Spinal anesthesia is a type of extensive nerve block by inserting a local anesthetic drug into the subarachnoid space at the lumbar level (Rehatta, 2019). This method produces anesthesia by blocking transmission, deactivating motor and sensory abilities, thus creating loss of pain sensation in the perineum. lower abdomen to lower extremities. Among the effects of spinal anesthesia that often occur, post-spinal anesthesia headache is a complication that often does not receive special attention. Due to the minor effects of spinal anesthesia. Management of headaches after spinal anesthesia, one of which is using non-pharmacological techniques with Head Up therapy, namely providing a 30 degree head elevation position with the aim of increasing blood flow to the brain in an effort to maximize oxygen flow to the brain which is believed to reduce the sensation of headaches. Objective: To analyze the effect of giving Head up therapy on headaches in post-operative patients with spinal anesthesia. Method: This research is a quantitative research using a type of experiment with a pre-experimental design, post-test control group design. Sampling technique: accidental sampling Population: The population of this study was 300 people. Sample: This study involved 76 respondents with a division of 38 respondents who were given Head Up therapy and 38 respondents who were not given Head Up therapy. Data analysis: Data were analyzed using the Mann Whitney test. The research instruments were Head Up SOP and Posttest Numeric Rating Scale (NRS) questionnaire. This research was carried out in February-April 2024 at Dr Hardjono Ponorogo Regional Hospital. Results: Based on research and after data analysis, the significance value (P value) in the Mann Whitney test was 0.001 (p>0.05). Conclusion: It was found that there was an effect of giving Head up therapy to post-operative patients with spinal anesthesia